Pády u hospitalizovaných pacientov – posudzovanie rizika - Bóriková, Ivana; Tomagová, Martina (Ošetrovateľstvo, 2016)
Aim: The aim of the paper is to find, to analyse and to compare guidelines and nursing standards with a focus on assessing the risk of falls inpatients/seniors. Methods: This is a review study. Guidelines and nursing standards were searched through the websites of selected professional societies, in February 2016, using the keywords: falls, prevention, risk assessment tool, adult, older, hospital, guideline. Documents that fulfil the required criteria were analysed with a focus on the issue of assessing the risk of falling. Results: The review includes the analysis and comparison of nine guidelines and nursing standards. Assessment the risk of falls inpatients is multifactorial. It is focused on identifying key risk factors; using a measurement tools for the screening of the overall risk of falling or specific risk factors, and other clinical and functional assessment. The most recommended screening tools include the Morse Fall Scale, Hendrich Fall Risk Model and STRATIFY. Assessment is basal for the selection and implementation of multifactorial interventions. Conclusion: Assessing the risk of falls is a key strategy for the prevention of falls. A standardized assessment method identifies key risk factors at the individual level and to target specific preventive interventions.
Keywords: rizikové faktory; Accidental Falls; směrnice jako téma; Risk Factors; lidé; hodnocení rizik; senioři; Inpatients; Guidelines as Topic; úrazy pádem; Aged; ošetřovatelská péče; Nursing Care; Patient Safety; hospitalizovaní pacienti; bezpečnost pacientů; Risk Assessment; Humans